Step * 1 of Lemma extend-name-morph-rename-one

.....wf..... 
1. Cname List
2. Cname List
3. name-morph(I;K)
4. Cname
5. z1 Cname
6. Cname
7. ¬(z1 ∈ I)
8. ¬(z ∈ I)
9. ¬(v ∈ K)
⊢ (rename-one-name(z;z1) f[z1:=v]) ∈ nameset([z I]) ⟶ extd-nameset([v K])
BY
(SubsumeC ⌜name-morph([z I];[v K])⌝⋅ THEN Auto) }


Latex:


Latex:
.....wf..... 
1.  I  :  Cname  List
2.  K  :  Cname  List
3.  f  :  name-morph(I;K)
4.  z  :  Cname
5.  z1  :  Cname
6.  v  :  Cname
7.  \mneg{}(z1  \mmember{}  I)
8.  \mneg{}(z  \mmember{}  I)
9.  \mneg{}(v  \mmember{}  K)
\mvdash{}  (rename-one-name(z;z1)  o  f[z1:=v])  \mmember{}  nameset([z  /  I])  {}\mrightarrow{}  extd-nameset([v  /  K])


By


Latex:
(SubsumeC  \mkleeneopen{}name-morph([z  /  I];[v  /  K])\mkleeneclose{}\mcdot{}  THEN  Auto)




Home Index